1987
DOI: 10.1111/j.1423-0410.1987.tb02987.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Human T Cell Lymphotropic Virus Type I by Blood Transfusion before and after Mass Screening of Sera from Seropositive Donors

Abstract: The human T cell lymphotropic virus type I (HTLV-I) is transmitted by blood transfusions that contain cell components as one of the virus transmission modes. We carried out mass screening of sera from seropositive donors by a gelatin particle agglutination test to prevent the spread of HTLV-I by transfusion. Seroconversion rates were compared before and after screening. The results show a remarkable decrease in the rate of infection from 53.6 to 0.9%. Therefore, it is certain that screening by the agglutinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…21 Afterwards the USA and other European countries (France, Luxembourg, Denmark, Holland, Sweden, and Belgium) have followed Japan's example. 15 39 In Spain, a study conducted in 1995 concluded that because of the low HTLV-I seroprevalence (0.002%) and poor sensitivity of serological determinations at that time, compulsory screening in blood banks was not justified.…”
Section: Discussionmentioning
confidence: 99%
“…21 Afterwards the USA and other European countries (France, Luxembourg, Denmark, Holland, Sweden, and Belgium) have followed Japan's example. 15 39 In Spain, a study conducted in 1995 concluded that because of the low HTLV-I seroprevalence (0.002%) and poor sensitivity of serological determinations at that time, compulsory screening in blood banks was not justified.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 12% of HTLV infections occur by blood transfusion. Unlike HIV-1, whole cell transfusion is required for transmission of the virus [90,91], with a seroconversion rate of approximately 50% [90,92]; however, the risk of transmission decreases markedly if the blood units are stored for more than six days before transfusion [91,93]. The development of HAM/TSP has been noted as early as six months after transfusion of an individual with infected blood [94].…”
Section: Viral Transmissionmentioning
confidence: 99%
“…Tax is not the only HTLV-1 antigen recognised by lymphocytes, but it has a position of special importance because it is the first HTLV-1 protein to be produced, and is a powerful mitogen and antigen. 6 Antigenic stimulation Tax as antigen Proliferating CD4 + help to maintain the high provirus load…”
Section: Figure 2 Human T Lymphotropic Virus Type 1 (Htlv-1) Infectiomentioning
confidence: 99%